Modelagem de nicho ambiental de espécies vegetais da caatinga como ferramenta para avaliação dos impactos das mudanças climáticas e do progresso das ods’s 13 e 15 no bioma semiárido brasileiro - Teixeira, Lucas Peixoto (2022)
Caatinga is an exclusive Brazilian ecosystem, which has a major extension of seasonal tropical dry forest (STDF). It is the STDF most biodiverse and densely populated in the world. Its biodiversity is threatened by anthropic pressure (as deforestation and fires) and has uncertain impacts by climatic changes. This ecosystem holds a variety of endemic fauna and flora species that has developed strategies to establishment themselves in an environment with water deficit. The semi-arid climate and water scarcity are the main limiting factors to this ecosystem, where drought is an agent of social and economic vulnerability. Climatological extreme events, increase of temperatures, and long droughts are concern in scenarios of climate changes. Furthermore, Caatinga has elevate rates of fragmentation, desertification cores and social scourge, which could be increased with climate changes. Biodiversity conservation and climate changes battle are within sustainable development goals (SDG 13 and 15) for 2030 Agenda. Thus, the aim of this work is assess estimated impacts due climate changes over the Caatinga representative biome flora. To achieve this, it used Environmental Niche Modelling for flora species, which allow compare the richness of species for the present conditions and for projected for climate changes scenarios. Furthermore, it intends assess the tendency of bioclimatic variables for this semi-arid ecosystem. Results shows for intense loss of environmental suitability for intermediary and pessimist scenarios, which could affect negatively flora richness species on Caatinga biome. Also, the are risks for generalized degradation when analysed the projections of bioclimatic variables, as long droughts, increase of climatological events and temperature rise. In addition, can be observe that Caatinga will face deep challenges do reach the aims of SDGs 13 and 15.